Pengaruh Modal Sosial pada Pembentukan Public Sphere di Twitter: Studi Kasus Isu Tes Wawasan Kebangsaan KPK dengan Pendekatan Kuantitatif Relasional - Meirza Luthfi Pradana (Departemen Politik dan Pemerintahan, Universitas Gadjah Mada, 2023)
This study discusses how social capital plays a role in increasing active engagement by netizens in the public sphere on social media. This paper uses the issue of the Corruption Eradication Commission's (TWK) national insight test as a case study. Because parties related to this issue, such as former KPK employees and so on, have made many tweets that have sparked public attention on Twitter. This study takes a relational quantitative approach through Social Network Analysis (SNA) and sentiment analysis in describing the findings. The data in this study was obtained from Twitter social media which has been processed by using the Big Data Analytics instrument. The data collection period is from May 16, 2021 to September 13, 2021. The results show that actors with high credibility in the real world seem to take advantage of their social capital when issuing tweets on Twitter. So that there is an increase in active involvement by netizens as evidenced by the existence of public support for the sampiran state institution, the KPK through the image of sentiment. The majority of sentiment images that have been collected in this study are dominated by negative sentiments or indicate contra toward the implementation of the KPK TWK.